Товариство з обмеженою відповідальністю "Нова Баварія" як приклад діяльності виробничих підприємств із змішаним (приватно-держаним) капіталом за часів НЕПу - Кабачек, Володимир Вікторович (НТУ "ХПІ", 2015)
У статі йдеться про часи НЕПу, коли було засноване і певний час проіснувало у вигляді товариства з обмеженою відповідальністю концесійного типу "Українське броварне товариство "Нова Баварія". До складу товариства увійшли Харківський губвиконком та громадянин Естонії І. І. Окман. Попри в цілому успішну роботу вказаного товариства, воно припинило свою діяльність через не пов'язані з м. Харковом причини. Робиться висновок про непослідовність дій державних органів, що ставило приватний капітал, у т.ч. – іноземний, у атмосферу невизначеності і надзвичайних ризиків.

The given paper e elucidates the period of New Economic Policy (NEP) when Ukrainian Brewery association "Nova Bavaria" ("New Bavaria") ltd of concession type was founded and existed a certain period of time. Its composition former on the basis of unprofitable trust of local industry "Brodcombinat" constituted as share-holders Kharkiv Province Executive Committee and the citizen of Estonia I. I. Okman. The very fact of the existence of the association mentioned above disproves the theses spread widely in historiography that at NEP period concessions as such and independent joint-stock companies with foreign and private financial capital did not exist. In spite of successful activity in general "Nova Bavaria" ceased its functioning not because of the reasons relating to Kharkiv and later continued its activity as a local industry trust Ukrainian "Nova (New) Bavaria" which to a certain time demonstrated successful indices. In conclusion is marked inconsistency of directing bodies actions that put private capital in general and foreign one in particular in the situation of uncertainty and extraordinary risks.
"Nova Bavaria" ("New Bavaria") associations ltd (limited) as an example of industrial enterprises with joint (private and state) financial actuary in the NEP years
Keywords: НЕП; Нова економічна політика; іноземні інвестиції; змішані товариства; приватно-державні товариства; NEP; New Economic Policy; enlisting foreign investments; joint (private and state) associations